Synthesis of pyrite nanoparticles for photovoltaic application - Hu, Ge (2016)
Iron disulfide (FeS2) or pyrite is a promising candidate material for photovoltaic application, because of its suitable bandgap of 0.95 eV, high absorption coefficient and good conductivity. Synthesizing pyrite with high purity is challenging and critical, because Fe-S system has many possible compositions, such as FeS, Fei-xS and Fe3S4, which may become byproducts during synthesis of pyrite and add sub-levels into the bandgap of pyrite. We use hot injection method for pyrite nanoparticles synthesis because it is an efficient way with small size and size distribution. We studied the effects of many experimental parameters systematically of which the S:Fe reactant ratio is the most critical. We clarify the difference between reactant ratio and precursor ratio. It was found that, the reason for S precursor to be in large excess during synthesis is to compensate for its weaker reactivity compared with Fe precursor. We have provided a rational explanation for using excess S and wam that a critical temperature should not be exceeded for pure pyrite synthesis. We show that TOPO could be used as a reaction modifier which could be used to expand the window of conditions for pure pyrite synthesis. We also highlight that if a S-deficient phase is formed, it cannot be sulphurized subsequently even if the S:Fe precursor ratio is raised sufficiently. Pyrite spherical nanoparticles, nanosheets and nanocubes have been synthesized in this project. Their forming mechanisms have been analysed individually. Pyrite spherical nanoparticles undergo a process of conventional nucleation and growth. Long time of reaction will result in increase in both size and size distribution of particles which could be attributed to Oswald ripening. In contrast, both pyrite nanosheets and nanocubes follow a different process, namely, nucleation, self-assembly and recrystallization. During the nucleation process, the transformation of FeS to FeS2 is also highlighted. Expanding reaction time will not cause significant change in size, because both nanosheets and nanocubes are terminated with {100} facets, which have tight bonding with the capping ligand used, OLA. A thermodynamic model is proposed to explain the effects of reactant (monomer) concentration on the particle coarsening mechanism and shape. To utilize the as synthesized pyrite nanoparticles, the capping ligands need to be removed because they are insulating. We achieved this by annealing the pyrite in sulfur atmosphere which preserved the pyrite phase. Annealing improved the conductivity of films fabricated from the particles by three orders of magnitude. The annealed pyrite/FTO film when used as counter electrode in dye sensitized solar cells gave conversion efficiency comparable to Pt counter electrode. Electrochemical analysis was done to characterize the pyrite film’s catalytic properties. Pyrite films made from spherical nanoparticles show the highest power conversion efficiency because of its larger reactive area.